Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1101/2020.10.26.20219600
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Head-to-head comparison of SARS-CoV-2 antigen-detecting rapid test with self-collected anterior nasal swab versus professional-collected nasopharyngeal swab

Abstract: Background: Two antigen-detecting rapid diagnostic tests (Ag-RDTs) are now approved through the WHO Emergency Use Listing procedure and can be performed at the point-of-care. However, both tests use nasopharyngeal (NP) swab samples. NP swab samples must be collected by trained healthcare personnel with protective equipment and are frequently perceived as uncomfortable by patients. Methods: This was a manufacturer-independent, prospective diagnostic accuracy study with comparison of a supervised, self-collect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 4 publications
4
83
0
1
Order By: Relevance
“…Sensitivities obtained in the present study were comparable to those observed in recent independent validation studies for the same Ag-RDT applied at this testing facility (73.2% to 80.5%) [10,11]. The slightly higher sensitivities in this study are likely due to the higher number of patients with a high viral load (72.5% with ≥7.0 log10 SARS-CoV-2 RNA copies/ml, versus 48.8% and 64.1% in the prior studies).…”
Section: Discussionsupporting
confidence: 88%
“…Sensitivities obtained in the present study were comparable to those observed in recent independent validation studies for the same Ag-RDT applied at this testing facility (73.2% to 80.5%) [10,11]. The slightly higher sensitivities in this study are likely due to the higher number of patients with a high viral load (72.5% with ≥7.0 log10 SARS-CoV-2 RNA copies/ml, versus 48.8% and 64.1% in the prior studies).…”
Section: Discussionsupporting
confidence: 88%
“…There were no controls delivered with the test devices by Roche and RapiGEN. (2,4,6,8) and negative controls (NCs) (1, 3, 5, 7) of four kits were performed, according to the manufacturer's protocol; (B) Controls of approach (A) were pooled and applied to the antigen tests by Roche (9,10) and RapiGEN (11,12). While the PC by Abbott also became positive with Roche (10), the BIOCREDIT test did not recognize the positive control (11).…”
Section: Resultsmentioning
confidence: 99%
“…During the review process of this manuscript, further studies were published that also investigated the utility of lateral flow antigen assays for the detection of SARS-CoV-2 and reported similar shortcomings in the overall performance of those assays. Lindner et al reported sensitivities of 74.4 to 79.5% in agreement with PCR assays, which meant that up to 25% positive cases were not detected by lateral flow assays [6]. Additionally, Weitzel and coworkers evaluated the usage of universal transport medium and its performance on lateral flow antigen devices [7], and revealed that sensitivities ranging from 16.7 to 85% depended on the subgroup of specimens tested.…”
Section: Discussionmentioning
confidence: 99%
“…Despite high specificity and sensitivity, rRT-PCR has a disadvantage in point of care testing, because it usually requires professional expertise, expensive reagents and specialized equipment. Therefore, alternative assays, such as rapid antigen detection tests, which can also detect the presence of the virus directly in respiratory samples, have been developed [ 4 ] and tested by different groups [ [10] , [11] , [12] , [13] , [14] ]. However, it is vital to determine the sensitivity, specificity of such tests relative to standard rRT-PCR in order to identify the ideal circumstances that their application would be beneficial.…”
Section: Introductionmentioning
confidence: 99%